Penerapan Bahasa Indonesia dalam Digitalisasi Arsip dan Dokumentasi Perkantoran - Padilah, Rizal; Ilmi, Raudia; Nadana, Rizal Lababa; Khairan, Rafi; Ramanda, Ramanda; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the application of the Indonesian language according to the rules in the digitization of archives and office documentation. This study uses a descriptive qualitative approach through a literature review of linguistic literature and digital archiving systems. The data collection technique involves reviewing various written sources such as books, scientific literature, notes, and reports relevant to the research issue. Data analysis is conducted through content analysis with steps to identify the linguistic aspects of the document and library sources. The research results show that many digital documents do not meet formal language standards, which impacts the clarity of information and the credibility of institutions. The use of non-standard language also complicates data retrieval and undermines the legal validity of documents. This study recommends the development of language guidelines, ongoing training for employees, and collaboration between language experts and information technology to ensure that the digitization of archives is not only technically efficient but also linguistically and administratively robust